Effects of probiotic supplementation on obesity markers in high fat diet-induced obese rats - Karimi, Golgis (2015)
Obesity and overweight are the major public health problems in the recent years. Some recent studies revealed that gut microbiota plays an important role in energy homeostasis and food intake in both human and animals. Therefore, this study aimed to investigate the effect of LcS and B. longum as a single strain and a combination on obesity and related metabolites in high fat diet-induced obese rats. A total of 50 male Sprague-Dawley (SD) rats at the age of 6 weeks were fed a standard diet for two weeks to stabilize all metabolic conditions and achieved ±200g weight. After two weeks, the rats were randomly selected and assigned to six groups (8 rats per group). Group 1 was fed with standard diet (SD) and group 2-6 were fed with high fat diet (HFD) (40% beef tallow) for 12 weeks. After 12 weeks of obesity induction 5ml blood were collected to measure lipid profile, inflammatory, anti-inflammatory and pro-inflammatory biomarkers. Besides rats were assigned into new six groups randomly. SD group fed by standard diet; HFD group fed high fat diet ; HFD-B.longum fed HFD HFD-orlistat fed by HFD and 10mg /kg body weight Orlistat, HFD-mix fed by HFD and the combination of LcS and B.longum. The rats were gavaged by probiotic (108 ~ 109 CFU) once a day for 15 weeks. Their body weight was measured weekly and body mass index (BMI) was calculated at week 12 and week 27 of the study. Besides, food intake of rats was measured daily. After 15 weeks of probiotic supplementation rats were sacrificed. Their blood was collected to measure the second round of serological biomarkers. Besides rats organs (liver, kidney, spleen and heart) were weighted. A small part of liver were cut and stored in RCL2 to measure the expression of some obesity related genes. Histological analysis was carried on the liver and adipose tissue. Probiotic supplementation either single strain or a combination made a reduction trend in body weight, fat mass, BMI and food intake. Between group analysis of lipid profile indicated that TG level in HFD group (1.25±0.44 mg/dl) was significantly higher than HFD-B.longum (0.57±0.11 mg/dl, P=0.02) and HFD-mix (0.68±0.27 mg/dl, P=0.049). Besides HFD-mix group had higher levels of HDL (1.5 ± 0.17 mg/dl) in comparison with HFD group (0.67 ± 0.07 mg/dl, p=0.001), HFD-B.longum (0.85 ± 0.1 mg/dl, p=0.001) and HFD-LcS (0.94 ± 0.11 mg/dl, p=0.004). No significant changes in LDL and cholesterol level were observed between HFD group with probiotic supplemented groups. Besides, present study depicted that inflammatory factors including IL-6, TNF-α and hs-CRP were remained constant in all treated groups. Leptin and adiponectin play an important role in energy intake and body weight management. In the present study over 15 weeks of probiotic supplementation leptin was significantly decreased and adiponectin was significantly increased in all treatment groups with no significant differences between single strain group with mixture group. These changes result in a reduction in body weight and food intake in all supplemented groups. Moreover, between groups analysis of leptin at week 27 showed that, rats supplemented by probiotic either single or a combination had lower concentration of leptin compared with HFD group (F= 3.24, p=0.017). In addition, adiponectin concentration was significantly higher supplemented groups as compared to HFD group (P ≤ 0.05). Furthermore, after 15 weeks of probiotic supplementation, expressions of PPAR-γ, ANGPTL-4 were up regulated while IL-6 expression was down. These changes decreased the lipid metabolism which consequently increases the fat excretion in feces. Increased expression of PPAR-γ lead to an increase in adiponectin secretion which lead to a decreased in food intake. Although the plasma level of IL-6 was not decreased, a significant reduction of IL-6 expression was observed at the molecular level. Therefore, prolong the probiotic period supplementation might result in inflammatory markers reduction. Results of the present study also demonstrated that probiotic supplementation in a dose of 108-109 CFU/day is a safe dose with no harmful singe or damage to liver and kidney. To sum up, this study observed that single strain of bacteria either LcS or B. longum has more beneficial health effect on obesity rather than the mixture.